DIPLOMASI PT.TOTAL EXPLORATION & PRODUCTION INDONESIE TERHADAP INDONESIA UNTUK MENDAPATKAN PERPANJANGAN KONTRAK MIGAS DI BLOK MAHAKAM - Halim, Helvi Tri Oktavianti; Rani, Faisyal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This research aims to explain diplomatic efforts of oil and gas company named Total Exploration and Production Indonesie in East Kalimantan. It originates from France and one of non-governmental company which has many wells in Indonesia. One of them is Mahakam Block, the country’s biggest gas block in terms of production which is located in Kutai, East Kalimantan.Sources were obtained from journals, books, internet, etc. In this research, the writer uses method of qualitative research. In addition, it uses analysis level of multinational corporation and pluralism perspective. The writer also uses multi-track diplomacy as theory of this research in order to know the kind of diplomacy track applied by Total Exploration and Production Indonesie.The problem in this research is about diplomatic efforts of Total Exploration and production Indonesie to get a contract extension of Mahakam Block which will be expired in 2017. Meanwhile, PT. Pertamina as Indonesia’s oil and gas company wants to take over the operation of Mahakam Block. Considering this situation , Total Exploration and Production must continue to look for ways and opportunities to negotiate with the Indonesian government to get a contract extension of Mahakam Block which has been managed by Total Exploration and production Indonesie almost for 50 years.Keywords : contract extension, East Kalimantan, Mahakam Block, PT.Pertamina,Total Exploration and Production Indonesie.